2012
DOI: 10.1089/jir.2011.0036
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 7 Ligands Inhibit Influenza A Infection in Chickens

Abstract: Avian influenza virus is endemic in many regions around the world and remains a pandemic threat, a scenario tied closely to outbreaks of the virus in poultry. The innate immune system, in particular the nucleic acid-sensing toll-like receptors (TLRs) -3, -7, -8, and -9, play a major role in coordinating antiviral immune responses. In this study we have investigated the use of TLR ligands as antivirals against influenza A in chickens. The TLR7 ligand poly-C inhibited low-path influenza A growth in the chicken m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 14 publications
3
29
0
Order By: Relevance
“…Although 6 hour pre-treatment was not the only time to significantly limit viral replication, it was selected for further analysis because it was the time when the greatest reduction of viral titre was observed for all three ligands. These results correlate with previous studies showing that pre-treatment with TLR7 ligands 6 hours prior to infection induced potent antiviral responses [23]. This suggests that a 6 hour pre-treatment of macrophages results in the early protection of the cells against AIV, which presumably relies on the TLR-mediated activation of antiviral responses.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although 6 hour pre-treatment was not the only time to significantly limit viral replication, it was selected for further analysis because it was the time when the greatest reduction of viral titre was observed for all three ligands. These results correlate with previous studies showing that pre-treatment with TLR7 ligands 6 hours prior to infection induced potent antiviral responses [23]. This suggests that a 6 hour pre-treatment of macrophages results in the early protection of the cells against AIV, which presumably relies on the TLR-mediated activation of antiviral responses.…”
Section: Discussionsupporting
confidence: 90%
“…It has recently been demonstrated that ligands for TLR2, 4 induce Th1-like and Th2-like responses while ligands for TLR21 induce Th1-like responses in chickens [19], [21], [22]. TLR ligands are also known to induce antiviral responses, including the induction of type I IFNs in chickens [22], [23]. Considering the immunostimulatory activities of TLR ligands, these molecules have been successfully used for conferring immunity on the host against viral and bacterial pathogens [24][27].…”
Section: Introductionmentioning
confidence: 99%
“…in the lung and brain in ducks, whereas the TLR7 mRNA expression in the lung and brain of the H7N1-infected chickens did not increase. According to Stewart et al (2012), the TLR7 ligand (loxoribine) can inhibit influenza A replication in vitro and in ovo. Perhaps the lack of the TLR7 response in the brain and lung of H7N1-infected chickens is related to an inadequate innate response of the host to clear the virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study reported that loxoribine induces antiviral gene expression such as type I IFN (IFN-α and IFN-β) and IFN-γ in primary chicken splenocytes, and can inhibit influenza A replication in vitro and in ovo in a dose-dependent manner [52]. However, R848 and poly(U) cannot stimulate chicken splenocytes to upregulate the expression of type I IFN, but it can cause increased expression of IL-1β, IL-6 and IL-8 [17].…”
Section: Toll-like Receptorsmentioning
confidence: 99%